the Antibacterial Potential of Gynura procumbens Against UTI Pathogens - Aminah, Siti; Tuntun, Maria (Poltekkes Kemenkes Tanjung Karang, 2025)
Cases of urinary tract infections (UTIs) in Indonesia continue to increase. According to data from the Ministry of Health (2014), UTI cases reach 90–100 per 100,000 population annually. The incidence of UTI is mainly caused by bacterial infections, particularly Escherichia coli and Klebsiella pneumoniae. One of the medicinal plants with pharmacological potential is the connected leaf (Gynura procumbens (Lour.) Merr.). This research aims to determine the effectiveness and impact of Gynura procumbens leaf extract at concentrations of 25%, 50%, 75%, and 100% in inhibiting the growth of E. coli and Klebsiella pneumoniae. This research employed an experimental and completely randomized design (CRD). The independent variables were the concentrations of Gynura procumbens extract, and the dependent variables were the UTI-causing bacteria (E. coli and Klebsiella pneumoniae). Each concentration treatment (25%, 50%, 75%, and 100%) was repeated six times. The results showed that the average inhibition zone for E. coli was 6.33 mm at 25%, 6.91 mm at 50%, 9.39 mm at 75%, and 13.24 mm at 100% concentration. For Klebsiella pneumoniae, the average inhibition zone was 6.56 mm at 25%, 7.53 mm at 50%, 12.50 mm at 75%, and 15.54 mm at 100%. One-way ANOVA analysis resulted in a p-value of 0.000, indicating that Gynura procumbens leaf extract significantly inhibits the growth of UTI-causing bacteria (Klebsiella pneumoniae and Escherichia coli).